Pengaruh Sistem Intercrop Padi Gogo - Rumput Terhadap Pertumbuhan Dan Hasil Padi Gogo - Yugi R Ahadiyat; T Harjoso; Ismangil Ismangil (Faculty of Agriculture, Pattimura University, 2014)
The objective of this study was to determine characters of several drought tolerance and high yield upland rice variety under low soil water content in intercrops rice – grass system. The study was carried out in rain water irrigation area of Banjaranyar village. Experimental design was Split Plot Design with three replicates. The Main plot was grass i.e no grass, elephant grass and lemon grass while sub plot was upland rice variety i.e. Situ Patenggang, Kalimutu, Danau Gaung, Jatiluhur dan Cisokan. Under very low soil water content (<12%), there was growth and yield differenc between rice varieties grown in intercrops system with grass. Eventhough there was no effect of this intercrop system on plant growth of upland rice, elephant grass promote higher rice yield, 0.88 t/ha than that without grass (0.39 t/ha) and with lemongrass (0.60 t/ha). Kalimutu variety showed the higher yield (1.38 t/ha) with plant height up to 46.27 cm and leaf area up to 4.63 cm2.